1997
DOI: 10.1016/s0014-5793(96)01455-x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechins such as (−)‐epicatechin and (−)‐epigallocatechin accelerate Cu2+‐induced low density lipoprotein oxidation in propagation phase

Abstract: Effects of (-)-epicatechin (EC) and (-)-epigallocatechin (EGC) on Cu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
3
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 19 publications
4
58
3
1
Order By: Relevance
“…37) However, in the present study, KBG did not show any pro-oxidative action, quite different from vitamin E. The reason for the discrepancy between the Kampo formulas (OGT and KBG) and vitamin E might be explained by the fact that a Kampo formulation consists of multiple ingredients (as shown in Figs. 1 and 2).…”
Section: Fig 1 Effects Of Kampo Medicines On Progression Of Atheromcontrasting
confidence: 65%
“…37) However, in the present study, KBG did not show any pro-oxidative action, quite different from vitamin E. The reason for the discrepancy between the Kampo formulas (OGT and KBG) and vitamin E might be explained by the fact that a Kampo formulation consists of multiple ingredients (as shown in Figs. 1 and 2).…”
Section: Fig 1 Effects Of Kampo Medicines On Progression Of Atheromcontrasting
confidence: 65%
“…Subsequent studies have revealed similar properties in other common antioxidants, including flavonoids [30], nonflavonoid phenols [36], cysteine [37,38], and urate [39][40][41]. The effects of ascorbate are further complicated by the fact that dehydroascorbate, the product of its two-electron oxidation, can itself act as both a pro-oxidant and an antioxidant toward LDL [24,26,35,42].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the epidemiological evidence indicating an inverse relationship between dietary fruit and vegetable intake and the incidence of cardiovascular disease [20,21], numerous studies have been undertaken to show that micronutrients provided by such diets, including α-tocopherol [22,23], ascorbic acid [24][25][26][27] and various flavonoids [28][29][30][31], can protect LDL from oxidative modification [32]. Under certain circumstances, however, they have been shown to display prooxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…These catechins have strong antioxidant activity (Rice-Evans, 1999;Dufresne and Farnworth, 2001;Higdon and Frei, 2003); they are potent scavengers of reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, hydroxyl radicals and nitric oxide produced by various chemicals (Guo et al, 1996;Vinson et al, 2002;Schroeder et al, 2003). It has been demonstrated that EGCG prevents spontaneous mutations (Mure and Rossman, 2001), LDL oxidation (Yamanaka et al, 1997) and chromosomal damage induced by ROS in somatic cells (Sugisawa and Umegaki, 2002;Roy et al, 2003). Sugisawa and Umegaki (2002) reported that a large amount of EGCG was present in cells after they were incubated with 0.3 µM EGCG.…”
Section: Introductionmentioning
confidence: 99%